Sport reserve training system optimization in elite basketball - Averyasova, Yu. O.; Filimonova, S. I.; Andryushchenko, L. B.; Andryushchenko, O. N.; Mostovaya, N. V. (Theory and Practice of Physical Culture, 2018)
The study analyzes findings of the research project to improve efficiency of the sport reserve training system applied in the national elite basketball. Applied for the study purposes were the competitive reporting data analyses, with the input data mined in the technical competitive records with a special emphasis on the technical and tactical match-specific performance and competitive load rating data. The reported data analysis gave us the grounds to offer recommendations on how the men`s national basketball team may be composed for the upcoming European championship based on the following: analysis of the individual performance in the United Basketball League using a variety of performance and pre-season fitness rating criteria; detailed tests and analyses in the training sessions; and systemic monitoring of individual performance in the training process using the relevant computerized test systems like ESTECK System that provides 100% accurate physical fitness rating test data. The coaching team shall apply the objective performance rating data to make timely adjustments to the individual and team training plans and game roles, with the offence and defense strategies and team management models being adjusted to benefit from the individual best qualities and skills.